A Note on the Gaps in the Support of Discretely Infinitely Divisible Laws. (17th December 2013) - Pakes, Anthony G.; Satheesh, S.
Abstract : We discuss the nature of gaps in the support of a discretely infinitely divisible distribution from the angle of compound Poisson laws/processes. The discussion is extended to infinitely divisible distributions on the nonnegative real line.